Terapia comunitária: um olhar crítico sobre sua trajetória na secretaria municipal de saúde de Santos/SP - Santos, Rosane Cristine dos [UNIFESP] (2015)
The Community Therapy (TC) is an intervention proposed by the Brazilian Unified Public Health System (SUS) which contributes to the strengthening of primary care and the principles of the Unified Health System (SUS), valuing the model of humanized attention and the expansion of National Policy for Integrative and Complementary Practices. In the municipality of Santos / SP, his practice has begun in 2006, through the Municipal Secretariat of Social Assistance, which funded the initial formation by offering twenty-four vacancies also to academic professionals from the Municipal Health Department. In 2009, It was performed the second fomation course, this time, with financial resources of the municipal health department, filling seventy-two vacancies for health professionals, social assistance and education, getting health with as many of them as it clearly showed the expansion of TC for the whole of primary care network. However, whether it was observed that most community therapists was gradually abandoning the wheels running in the city of Santos. In addition, changes in management teams, made the TC ceased to be emphasized and prioritized. This research has as objective investigate the representation of TC in Municipal Health Department at the present moment, from the perspective of managers, community therapists and representatives of local health teams in an attempt to analyze and understand the continuous movement of decreased community therapists in the exercise of that function. It seeks to understand whether TC is recognized as a health promotion tool and as an integrative practice addition and also recognize its impact from the health teams. This study was developed through of qualitative research, being used as instruments to collect interviews and documental research. The interview analysis was performed using the collective subject discourse method (DSC), chosen because it presents as characteristic the extraction of collective thought and the social representation of the theme. The study subjects were three managers, six community therapists and three heads of health facilities. The central theme is the TC and, from there, connections were established with guiding themes of the SUS and health policies related to the proposed objectives. So, they are presented as input of thematic Care and Health Promotion, Integrality and Permanent Education, Popular Education and Health Education and Integrative and Complementary Practices. The results indicate that the decrease in TC wheels in the city may be linked to lack of encouragement by local managers, the distorted conception on health promotion linked to the idea of prevention, lack of complementary integrative practices in the SUS and the appreciation of the model focused attention on the doctor. In this way, the continuity and strengthening of TC are directly related to the need for investment in Permanent Education as a strategy discussion of care practices managed to Integrative and Complementary Practices.